Pengaruh Citra Merek Dan Kualitas Layanan Terhadap Kepuasan Nasabah Di Bank Syariah Indonesia - Permatasari, Melisa Devi; Istiqomah, Nur Hidayatul (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This study examines the influence of brand image and service quality on customer satisfaction at BSI Tuban City through a quantitative approach using purposive sampling technique and multiple linear regression analysis. The research findings reveal that brand image has a significant effect of 30.71% with a probability of 0.003, while service quality has a greater influence of 44.59% with a probability of 0.000. Collectively, brand image and service quality significantly impact customer satisfaction with a coefficient of 46.15% and a probability of 0.000. The research conclusion emphasizes that service quality has a more dominant contribution compared to brand image in influencing customer satisfaction, therefore recommending that BSI should continue to improve service quality and maintain its brand image. Future research is expected to explore additional factors such as cost, location, and promotions that potentially affect customer satisfaction in the context of sharia banking.